Multitemporal analysis of the urban expansion of the municipality of Garanhuns - PE, through remote sensing - Deus, Rodolfo Alexandre da Silva Gomes de; Ramos, Renilson Pinto da Silva; Costa, Samuel Othon de Souza; Gomes, Daniel Dantas Moreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper aims to use the remote sensing analysis of urban expansion, seeking to improve the identification of growth áreas of the city and the best way to understand the growth and expansion of the city. The studies are based on the municipality of Garanhuns, the interior of Pernambuco. Remote sensing ends providing greater speed and objectivity in the process as well as bring a greater number of data for analysis and thus can serve as a basis for current and future planning and provide information for control and knowledge of the area in question. For analysis beyond the NDBI Remote sensing was used as identification of targets selected index by its characteristics highlight the bodies of building and construction amid the electromagnetic spectrum, it was the best choice to make the most accurate and current job in fostering data was used satellite images obtained by LANDSAT-5 provided by USGS, such images were treated with 10.2.2 software ARCGIS, aiming to extract the greatest possible amount of information for better understanding of the object of study.